Artefact-driven narrative literature review (ART-NLR): Supporting evidence synthesis for design science research - Trigo, A. (Journal of Documentation, 2026)
Purpose This paper introduces the artefact-driven narrative literature review (ART-NLR), a literature review approach designed to support design science research (DSR). Conventional systematic review guidelines assume a single, front-loaded review and are poorly suited to iterative design research where literature must inform multiple decisions. ART-NLR addresses this gap by structuring literature engagements around DSR activities, enabling focused evidence synthesis that supports problem definition, design requirements, artefact development and evaluation. Design/methodology/approach ART-NLR aligns literature engagement with key DSR activities: problem identification, solution objectives definition, design and development, and evaluation. Each review follows a four-step process: research question and gap definition, search strategy execution, corpus screening and consolidation, and structured narrative synthesis. The approach integrates heterogeneous evidence and translates findings into design-relevant outputs, while maintaining transparency in search decisions and allowing iterative refinement as new knowledge needs emerge during the research process. Findings The study presents ART-NLR as a structured narrative review method tailored to design-oriented research. By linking literature reviews to decision points in the DSR cycle, the approach enables researchers to derive actionable knowledge that informs artefact design and evaluation. ART-NLR demonstrates that narrative synthesis, when conducted systematically and transparently, can support iterative evidence use without the procedural overhead of comprehensive systematic reviews. Research limitations/implications ART-NLR prioritises problem relevance and design utility rather than exhaustive evidence aggregation and is therefore not intended for comprehensive evidence synthesis. Outcomes depend on the clarity of the research problem and the researcher’s judgement during review scoping and interpretation. Future research should empirically compare ART-NLR with other review approaches and examine its transparency, reliability and pedagogical value in design science and applied research contexts. Practical implications ART-NLR offers researchers and educators a pragmatic method for structuring literature reviews within iterative design research projects. The approach helps translate prior knowledge into problem statements, design requirements, implementation decisions and evaluation criteria. It is particularly useful in DSR-based student research and applied projects where time and resource constraints make comprehensive systematic reviews impractical. Social implications By supporting more transparent and evidence-informed artefact design, ART-NLR can improve the development of technological, informational and educational interventions addressing complex societal problems. Structured engagement with prior knowledge strengthens the credibility of design decisions and promotes more robust, context-sensitive research outcomes. Originality/value This paper introduces ART-NLR, a novel literature review approach that reconceptualises narrative reviews as artefact-driven evidence syntheses aligned with DSR. The study extends review typologies by demonstrating how structured narrative synthesis can systematically support artefact design and evaluation across iterative research cycles, providing practical methodological guidance for design science researchers and educators.